How Is the COVID-19 Crisis Exacerbating Socioeconomic Inequality among Palestinians in Israel? - Sami H. Miaari; Maha Sabbah-Karkabi; Amit Loewenthal (Institute of Labor Economics (IZA), 2020)
The paper gives us a first look on the unique effects of the crisis on the Arab minority in Israel. It contributes to our understanding on how economic and epidemic crises affect marginalized ethnic minorities and informs decision makers while formulating policies to deal with the crisis's consequences. The results of the paper show significant differences between how this minority group was affected by the crisis compared to the majority-Jewish population. Two months into the crisis, there was no significant difference between the employment rate of low and middle-paid Arab workers, who both suffered employment decreases, but in similar rates. This result is contrary to Jewish workers, where the more workers were paid before the crisis, the more likely they were to remain employed. The research is based on a unique survey conducted during the months of April and May, intended the first wave of a panel survey conducted every 3 months during the coming two years.
Keywords: I14; J15; J21; J64; 330; COVID-19; inequality; minorities